Evaluasi Program Layanan Oke Masyarakat Keliling (LOMAK) di Kecamatan Rumbai Kota Pekanbaru - Ikhlas Alzaref; Febri Yuliani (Universitas 17 Agustus 1945 Semarang, Indonesia, 2023)
The Mobile Community Oke Service Program (LOMAK) is an innovation from the Rumbai District Head in the field of public services which aims to make it easier for people in Rumbai District to get various public services. The LOMAK program itself is a form of integrated sub-district administrative service (PATEN) which is deployed to serve administration in the middle of community settlements or can be said to be an integrated sub-district administrative service around. However, in its implementation the LOMAK Program did not run well. In 4 years the LOMAK Program was only implemented 3 times, while the LOMAK Program should have been implemented once a month. This research aims to evaluate the Mobile Community OK Service Program and the factors that hinder its implementation. The research method used is a descriptive qualitative method and uses policy evaluation theory according to William N. Dunn which consists of several indicators, namely effectiveness, efficiency, adequacy, alignment, responsiveness and accuracy. The results of this research are that the LOMAK Program is a very good program. Of the 6 indicators above, only 1 indicator was not met, namely efficiency in terms of time. The inhibiting factors in implementing the LOMAK Program are natural disasters and the managerial abilities of implementers. Researchers provide suggestions so that implementers can find a backup plan in the event of a natural disaster and increase outreach so that the LOMAK Program can reach all levels of society.